ANALISIS METODE KRITIK HADITS DAN PANDANGAN HUKUM INDONESIA TERHADAP BERITA HOAX - Derry Angling Kesuma (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
Internet users in Indonesia have reached 196.7 million users. This industrial era 4.0 allows users to access, obtain and disseminate news and information more easily at any time, but this also makes it easier to spread hoax news. This research is a qualitative research with comparative-juridical analysis. The data obtained in the form of secondary data, obtained through a literature review. The analysis is based on liturgical analysis from various data sources that are considered valid, based on the conditions experienced by society today. The research methodology consists of a descriptive approach and a library approach. From the results of this study, it can be seen that the Hadith criticism method can be a reference for the community to verify whether the news received is whether there are additions (ziyādah), insertions (idrāj), reversals (iqlāb), or subtractions (nuqshān), and whether the substance is appropriate with reality or not. Meanwhile, according to Indonesian law, there is Article 45a which regulates threats to spreaders of fake news and a maximum imprisonment of six years, with a maximum fine of Rp. 1,000,000,000,- (One Billion Rupiah) and those who spread fake news are confirmed to have violated Article 28 (1) of Law Number 11 of 2008 which regulates Information and Electronic Transactions.